2023
DOI: 10.1001/jamaoncol.2023.2271
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Severity and Waning Immunity After up to 4 mRNA Vaccine Doses in 73 608 Patients With Cancer and 621 475 Matched Controls in Singapore

Abstract: ImportanceDespite patients with cancer being at risk of poor outcomes from COVID-19, there are few published studies for vaccine efficacy in this group, with suboptimal immunogenicity and waning vaccine efficacy described in small studies being a concern.ObjectiveTo assess the incidence rate of severe COVID-19 disease outcomes associated with the number of vaccine doses received and the waning of protection over time.Design, Setting, and ParticipantsA prospective multicenter observational cohort study was carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 47 publications
2
4
0
Order By: Relevance
“…A study described a similar finding in relation to the time since second vaccine dose [41]. This finding is consistent with waning vaccine immunity that has been previously described [42][43][44][45][46]. Our study also highlights the increased risk of Omicron SARS-CoV-2 infection among vaccinated individuals from Hispanic, Asian, and Black ethnic/racial groups.…”
Section: Discussionsupporting
confidence: 91%
“…A study described a similar finding in relation to the time since second vaccine dose [41]. This finding is consistent with waning vaccine immunity that has been previously described [42][43][44][45][46]. Our study also highlights the increased risk of Omicron SARS-CoV-2 infection among vaccinated individuals from Hispanic, Asian, and Black ethnic/racial groups.…”
Section: Discussionsupporting
confidence: 91%
“…Our study revealed that those who did not seroconvert after they completed a primary vaccination series and booster doses as recommended by the US FDA for immunocompromised individuals [19] may develop antibodies with additional vaccine doses. Our data are supported by a larger nationwide cohort study conducted in Singapore which showed that cancer patients received significant protection against severe COVID-19 with a third dose of vaccine and were further protected after a fourth dose of vaccine [20] . Although the benefit of fifth and sixth doses of vaccine is still uncertain, one of our patients acquired additional vaccine doses outside of existing guidelines and successfully seroconverted after six total doses of vaccine.…”
Section: Discussionsupporting
confidence: 77%
“…All but one of these patients, three weeks after the fourth dose, developed positive levels of anti-spike antibodies [ 25 ]. Recently, a nationwide cohort study from Singapore has provided evidence of the clinical effectiveness of mRNA-based fourth booster dose vaccines against COVID-19 in patients with cancer [ 26 ]. However, this study revealed some limitations, as reported by the authors themselves: the study may have been objected to confounding variables that could not be controlled for [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a nationwide cohort study from Singapore has provided evidence of the clinical effectiveness of mRNA-based fourth booster dose vaccines against COVID-19 in patients with cancer [ 26 ]. However, this study revealed some limitations, as reported by the authors themselves: the study may have been objected to confounding variables that could not be controlled for [ 26 ]. In our hospital, a task force charged with promoting the importance of the COVID-19 vaccine for cancer patients has been established since February 2021.…”
Section: Discussionmentioning
confidence: 99%